Patchworking Library Services for Invisiblized Youth - Rae-Anne Montague; Joseph A. Coyle (The International Journal of Information, Diversity, & Inclusion, 2019)
Librarians find themselves continuously challenged to provide a growing range of innovative services. In order to succeed, this complex task is grounded in local context and implemented based on the needs of users, be it students, patrons, clients, or community members. This article considers parameters of and discusses strategies for developing library services to meet the needs of incarcerated youth. How can librarians be effective in serving these young people who have been drawn into atypical realms, away from their communities, away from the Internet? There is a clear and urgent need to provide excellent library services to the approximately 60,000 youth incarcerated across the U. S. Currently, there are groups that emphasize services to these users. For example, Library Services for Youth in Custody (LSYC) is a professional interest group that focuses on providing a network to support these services. Other agencies are also involved, often as part of outreach programs, special projects, or on an ad-hoc basis. Together, these efforts result in a patchwork of services. In this case study, we draw on the experience of several dedicated individuals and groups that work to form a patchwork for building awareness, sharing resources, and meeting the informational needs of incarcerated youth. We critically consider these matters in theory and practice while reflecting back on the ten years of providing library services at a youth detention facility located in the U.S. Midwest; like many similar facilities, it has no librarian, no other library staff, and no regular library budget.